Okul dışı fiziksel aktivite programlarına katılan ve katılmayan öğrencilerin akademik başarılarının araştırılması - Yılmaz, Şevki (My University, 2019)
Bu çalışmanın amacı ilköğretim 5. ve 6. Sınıfta eğitim gören kız ve erkek öğrencilerden okul dışı fiziksel aktivite programına katılan ve katılmayanların motorik özellikleri ile akademik başarıları arasındaki ilişkiyi incelemektir. Bu araştırma İstanbul ili Başakşehir ilçesinde 5. ve 6. sınıfta eğitim gören okul dışında fiziksel aktivitelere katılan ve katılmayan (kız ve erkek) öğrencilerin motorik - antropometrik ölçümleri, akademik başarı düzeyleri ve dikkat düzeyleri arasındaki farkları belirlemek için yapılmıştır. Bu araştırmanın evrenini İstanbul ili Başakşehir İlçesi 5. ve 6. sınıf öğrencileri oluşturmuştur. Örneklem grubunu 2018-2019 eğitim öğretim yılında İstanbul ili Başakşehir ilçesinde yer alan Milli Eğitim Bakanlığı’na bağlı Hikmet Uluğbay Ortaokulunun 5. ve 6. sınıflarında öğrenim gören öğrenciler oluşturmaktadır. Fiziksel aktivite yapan ve fiziksel aktivite yapmayan öğrenciler anket yöntemi ile belirlenmiştir. Bu araştırmada fiziksel aktiviteye katılan ve fiziksel aktiviteye katılmayan öğrencilerin veri toplama araçları olarak akademik başarı düzeyleri, dikkat düzeyleri, atletik performans ve motorik test ölçümleri (otur uzan testi, şınav ve mekik testi, el pençe kuvveti testi, flamingo denge testi, durarak uzun atlama testi, 10 ve 20 metre sprint testi, zig-zag çeviklik testi) kullanılmıştır. Beşinci ve altıncı sınıfları kapsayan ortaokul öğrencilerinin burdon dikkat test sonuçları, antropometrik ölçüm sonuçları, fiziksel ve fizyolojik test değerleri ve akademik başarı düzeyleri tespit edilerek bağımsız örneklemler arasındaki ilintilerin değerlendirildiği bu araştırmada ilişkisel tarama yöntemi kullanılmıştır. İlişkisel tarama modelleri, iki ve daha çok sayıdaki değişken arasında birlikte değişim varlığını ve/ veya derecesini belirlemeyi amaçlayan araştırma modelleridir ( Karasar, 2013, s.81). Akademik Başarı puanı değerlendirmesinde öğrencilerin yılsonu başarı puanları dikkate alınmıştır. Öğrencilerin cinsiyet, motorik özellikleri, burdon dikkat testi verileri spss ortamında analiz edilerek yorumlanmıştır. Çalışmada kullanılan istatistiksel analizler % 95 güven aralığında 0,05 hata düzeylerinde gerçekleştirilmiştir.Sonuç olarak okul dışı fiziksel aktivite programına katılan ve katılmayan kız-erkek öğrencilerin dikkat düzeyleri arasında anlamlı bir farklılık bulunmuştur (p<0.05). Okul dışı fiziksel aktivite programlarına katılan ve katılmayan öğrencilerin motorik özellikleri arasında anlamlı farklılıklar bulunmuştur (p<0.05). Okul dışı fiziksel aktivite programlarına katılan ve katılmayan kız-erkek öğrencilerin Akademik Başarı puanlarıivarasında farklılıklar bulunmuştur (p<0.05). Kız ve Erkek öğrenciler arasında motorik özellikler açısından farklılıklar bulunmuştur (p<0.05).

The aim of this study is to investigate the relationship between the motoric-oriented and academic achievements of the girls and boys in the 5th and 6th grades of secondary education who participate and don’t participate the activities of the out-of-school activity program. In accordance with this purpose some studies are done to determine the differences of the motoric-anthropometric measurements, academic achievements and attention levels of the girls and boys in the 5th and 6th grades of secondary school who participate and don’t participate in the physical activities. The sample group consists of totally 533 students (N:218 girls, N:315 boys) who are in the 5th and 6th grades of Hikmet Uluğbay secondary school where is affiliated to ministry of national education in 2018-2019 education year in İstanbul in Başakşehir.533 students who participate in the study are divided into two groups as physical activities are done and not done. The group of students who participate in physical activities(N:32 girls, N:102 boys),the group of the students who get educated in the last six months,the group of the students who do exercises actively at least 2 days 2 hours are determined by questionnaire method.Out of those groups are supposed that they don’t participate in the physical activities and the groups are created (N:186 girls,N:213 boys).According to questionnaire results the students who participated in physical activities but didn’t participate in measurements are not considered in evaluation. In this study, academic achievement levels, attention levels, athletic performance and motor test measurements (sit-down test, push-up and shuttle test, hand-claw strength test, flamingo balance test, standing long jump test) , 10 and 20 meters sprint test, zig-zag agility test) are used as data collection tools for the students who participate in and don’t participate inphysical activities. The relational screening method is used in this study, where the correlations between independent samples were evaluated by determining burdon attention test results, anthropometric measurement results, physical and physiological test values and academic achievement levels of the fifth and sixth grades of secondary school students. These are research models aiming to determine the existence of change and / or degree of change together between two or more variables. (Karasar, 2013, p.81).While evaluating the academic achievement, the scores of the students in the end of the year are taken into considiration. Gender and motor characteristics, data of the burdon attention test of the students are interpreted by analizing in spss environment. Thevistatistical analyzes used in the study are carried out at 95% confidence interval and 0.05 error levels. As a result, a significant difference is found between the attention levels of the male and female students who participated in and didn’t participate out of school physical activity program (p<0.05). Significant differences are found between the Academic Achievement scores of male and female students who participated in and didn’t participate out of school physical activity programs (p<0.05). Differences are found between male and female students in terms of motoric characteristics (p<0.05).
Keywords: Akademik Başarı; Attention level; Dikkat Seviyesi Academic Achievement; Motor Beceri testleri; Motor skill tests; Öğrenim ve öğretim; Spor; Sports; Study and teaching